PENERAPAN MODEL PEMBELAJARAN MIND MAPPING UNTUK MENINGKATKAN HASIL BELAJAR IPAS SISWA KELAS IV SD KATOLIK I WOLOAN - Dea Oktavia Sirait; Jeanne M. Mangangantung; Fonny Katili (STKIP Subang, 2026)
ABSTRACKThis research was undertaken with the objective of enhancing students’ academic performance in the domain of Natural and Social Sciences (IPAS) through the implementation of the Mind Mapping pedagogical model for fourth-grade pupils at SD Katolik I Woloan. The rationale behind this investigation stems from the comparatively inadequate student learning outcomes, as evidenced by the observation that a subset of students had not met the Minimum Mastery Criteria of Learning Objectives (KKTP) stipulated by institutional standards. The methodological approach employed in this inquiry is Classroom Action Research (CAR), which adheres to the Kemmis and McTaggart cyclical framework encompassing the phases of planning, action, observation, and reflection, and was executed over two distinct cycles. Data collection methodologies were implemented through assessments of academic achievement and systematic observations of pedagogical activities involving both educators and learners throughout the instructional process. The findings of the study indicated a progressive enhancement in student academic performance across each cycle. In the initial cycle, the collective mastery level attained was 71.36%. Subsequent to the implementation of targeted improvements in the second cycle, the mastery level exhibited an increase to 88.2%. Moreover, the integration of the Mind Mapping model also yielded beneficial effects on amplifying student engagement, fostering collaborative skills during group tasks, and enhancing students’ competencies in organizing and articulating the results of Mind Mapping activities. In light of these results, it can be inferred that the application of the Mind Mapping learning model is efficacious in advancing students’ academic outcomes in IPAS for fourth-grade learners at SD Katolik I Woloan. Consequently, this model may be regarded as an innovative and readily implementable alternative instructional strategy within elementary educational contexts ABSTRACT This research was undertaken with the objective of enhancing students’ academic performance in the domain of Natural and Social Sciences (IPAS) through the implementation of the Mind Mapping pedagogical model for fourth-grade pupils at SD Katolik I Woloan. The rationale behind this investigation stems from the comparatively inadequate student learning outcomes, as evidenced by the observation that a subset of students had not met the Minimum Mastery Criteria of Learning Objectives (KKTP) stipulated by institutional standards. The methodological approach employed in this inquiry is Classroom Action Research (CAR), which adheres to the Kemmis and McTaggart cyclical framework encompassing the phases of planning, action, observation, and reflection, and was executed over two distinct cycles. Data collection methodologies were implemented through assessments of academic achievement and systematic observations of pedagogical activities involving both educators and learners throughout the instructional process. The findings of the study indicated a progressive enhancement in student academic performance across each cycle. In the initial cycle, the collective mastery level attained was 71.36%. Subsequent to the implementation of targeted improvements in the second cycle, the mastery level exhibited an increase to 88.2%. Moreover, the integration of the Mind Mapping model also yielded beneficial effects on amplifying student engagement, fostering collaborative skills during group tasks, and enhancing students’ competencies in organizing and articulating the results of Mind Mapping activities. In light of these results, it can be inferred that the application of the Mind Mapping learning model is efficacious in advancing students’ academic outcomes in IPAS for fourth-grade learners at SD Katolik I Woloan. Consequently, this model may be regarded as an innovative and readily implementable alternative instructional strategy within elementary educational contexts